Diretrizes para a melhoria da gestão do processo de projeto de edifícios multipavimentos - CASTRO, Moema Patricia Barros de (2010)
This study examines the design process management and its interrelation with the constructive process of multifamily residential buildings. Based on an exploratory survey to identify and understand the methodologies for managing the design activity into two companies in the metropolitan region of Goiania, this work is divided into three phases: literature review, desk research and field research (based interviews with key players in the process). To support this work in the investigation of major issues influencing the design process, one of the key steps in the roadmap construction work was the adoption of two reference models: (i) the reference model for building integrated design process management proposed by Romano (2003), and (ii) the manuals scope of projects and services for the real estate industry (AGESC, 2010). These models helped in the development of a roadmap for semi-structured individual and group members with different professional process in two companies. With the purpose of fostering multidisciplinary cooperation and integration between different actors, the results of this study may be relevant to people who will handle or manage projects so that they can reflect on how to improve the postures adopted by the guidelines prepared and that they cast in development of practices and progress of the project management of buildings.